2022
DOI: 10.1039/d2nj01139e
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-induced self-assembly transformation: an effective external stimulus on 2D supramolecular structures

Abstract: With the development of nano-characterization technology, imaging and controlling of two-dimension (2D) self-assembled supramolecular structures on the surface have drawn increasing attention in nanoscience and technology. As an important influence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In general, in solution-based self-assembly processes, higher temperature can lead to higher molecule mobilityaltering the dispersion forces of the pi–pi stackingand can therefore lead to structural phase transitions by overcoming the kinetic limitations. We investigate the impact of temperature on the self-assembling process by adding C8S3 monomers to aqueous solution preheated at different temperatures ranging from room temperature (23 °C), 55 °C, 70 °C, 85 °C, up to 100 °C, respectively. Furthermore, for cyanine dye, it was previously found that environmental conditions such as the type of counterion accompanying the chromophores of dye molecules may influence the morphology of the resulting supramolecular assemblies Here, the C8S3 dye monomers (used as received) are accompanied by Na + as counterions as described in the Method Section.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In general, in solution-based self-assembly processes, higher temperature can lead to higher molecule mobilityaltering the dispersion forces of the pi–pi stackingand can therefore lead to structural phase transitions by overcoming the kinetic limitations. We investigate the impact of temperature on the self-assembling process by adding C8S3 monomers to aqueous solution preheated at different temperatures ranging from room temperature (23 °C), 55 °C, 70 °C, 85 °C, up to 100 °C, respectively. Furthermore, for cyanine dye, it was previously found that environmental conditions such as the type of counterion accompanying the chromophores of dye molecules may influence the morphology of the resulting supramolecular assemblies Here, the C8S3 dye monomers (used as received) are accompanied by Na + as counterions as described in the Method Section.…”
Section: Results and Discussionmentioning
confidence: 99%
“…80 In addition, competition between various parameters may favor an organization over another and may lead to a phase transition within the same system. For example at the molecular scale, the final structure can be influenced by temperature, 81 surface defects, 82 concentration, 52,83 or force competition. 84 At the nanoscale, the ratio between the core radius and the ligand chain length is an efficient tool to control the final structure of binary nanocrystal superlattices.…”
Section: Discussionmentioning
confidence: 99%